2016
DOI: 10.1002/hyp.10984
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ‘two water worlds’ hypothesis and water sources for native and exotic evergreen species in south‐central Chile

Abstract: Recent studies using water-stable isotopes (δ 18 O and δ 2 H) have suggested an ecohydrological separation of water flowing to streams or recharging groundwater and water used by trees, known as the 'two water worlds' (TWW) hypothesis. In this study, we measured water isotopic composition in precipitation [open field and throughfall, i.e. local meteoric water line (LMWL)] and the mobile water compartment (i.e. stream and soil solution), bulk soil water and xylem water over a period of 1.5 years in two headwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 77 publications
4
113
2
Order By: Relevance
“…While comparisons of the isotopic signal in soil waters with waters of plant tissues have been reported for decades (see review by Ehleringer and Dawson, 1992), recently posed research questions on which water of the soil's pore system is used by plants (Brooks et al, 2010) are enhancing ecohydrological studies on soil-plant interactions in the critical zone. While studies based on two sampling campaigns (Goldsmith et al, 2012;Evaristo et al, 2016) were supportive of the ecohydrological separation, as presented by Brooks et al (2010), newly published work with higher temporal resolution of soil water and xylem water isotope sampling suggests that there are seasonal differences with regard to ecohydrological separation (McCutcheon et al, 2016;Hervé-Fernández et al, 2016). A comparative study by Evaristo et al (2015) showed that the isotopic composition of plant waters -just like soil waters in the upper horizons -are usually kinetically fractionated.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While comparisons of the isotopic signal in soil waters with waters of plant tissues have been reported for decades (see review by Ehleringer and Dawson, 1992), recently posed research questions on which water of the soil's pore system is used by plants (Brooks et al, 2010) are enhancing ecohydrological studies on soil-plant interactions in the critical zone. While studies based on two sampling campaigns (Goldsmith et al, 2012;Evaristo et al, 2016) were supportive of the ecohydrological separation, as presented by Brooks et al (2010), newly published work with higher temporal resolution of soil water and xylem water isotope sampling suggests that there are seasonal differences with regard to ecohydrological separation (McCutcheon et al, 2016;Hervé-Fernández et al, 2016). A comparative study by Evaristo et al (2015) showed that the isotopic composition of plant waters -just like soil waters in the upper horizons -are usually kinetically fractionated.…”
Section: Introductionmentioning
confidence: 93%
“…In line with the call for a higher temporal resolution of soil water isotope sampling (Berry et al, 2017), the highly dynamic isotopic signal during the transition between the dormant and growing seasons underlines the importance of not limiting the soil water isotope sampling to a few sampling campaigns (usually n ≤ 3 in Brooks et al, 2010;Evaristo et al, 2016;Goldsmith et al, 2012), when investigating root water uptake patterns. In the light of recent studies dealing with potential water sources of vegetation that showed how variable the plant water isotopic signal can be over a year (Hervé-Fernández et al, 2016;McCutcheon et al, 2016), a proper understanding of the temporal variability of the potential water sources (i.e., bulk soil water, groundwater, stream water) appears to be critical.…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 99%
“…Ehleringer and Dawson, 1992;Dawson et al, 2002;Volkmann et al, 2016;Rothfuss and Javaux, 2017), and identifying plant water sources (e.g. Brooks et al, 2010;Dawson and Ehleringer, 1991;Dawson and Simonin, 2011;Goldsmith et al, 2012;Evaristo et al, 2015;Hervé-Fernández et al, 2016;McCutcheon et al, 2017). A recent review by Sprenger et al (2016) 5 provides an extensive overview of isotope-based studies in the unsaturated zone.…”
mentioning
confidence: 99%
“…Evaristo et al, 2015;Hervé-Fernández et al, 2016;Javaux et al, 2016), as well as groundwaters (e.g. Dogramaci et al, 2012) and streamwaters (e.g.…”
mentioning
confidence: 99%
“…From the moment that this hypothesis has been stated, it has been tested in many sites across the globe, including Mexico (Goldsmith et al, 2011), Italy (Penna et al, 2013), Chile (Hervé Fernández et al, 2016), Utah (Bowling et al, 2017;Oerter & Bowen, 2017), New Zealand (Dudley, Marttila, Graham, Evison, & Srinivasan, 2017), China (Qian et al, 2017;Zhao, Tang, Zhao, & Tang, 2018), and others. According to the suggestions about future directions presented in McDonnell (2014) and Berry et al (2018), related work is still needed in contrasting climates and vegetation regimes and practical issues regarding different extraction techniques of plants and soil water.…”
mentioning
confidence: 99%